Background levels of heavy metals in the water of Khadzhibey estuary - O. O. Holubenko; L. O. Tarasenko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
In the Odesa region, heavy metal contamination of fishery water bodies is a pressing problem. The accumulation of heavy metals in fish depends on the physiological and biochemical activity of the organism and the physical and chemical parameters of the water body. Most heavy metals enter the fish's body through the gills, skin, and digestive organs. Copper, zinc, and plumbum accumulate in the skin, gills, and liver, while cadmium and mercury accumulate in the kidneys. The level of heavy metal pollution in the water of the Khadzhibey estuary was measured and determined in 2022–2023. The following methods were used to determine the content of heavy metals in water: atomic emission spectroscopy using an EMAS-200 CCD instrument to determine cadmium, copper, zinc, and plumbum; cold vapor atomic absorption spectroscopy using the “Julia-2M” method to determine the content of mercury. Toxicological studies of water were carried out in the water hygiene and ecology laboratory of the Ukrainian Research Institute of Transport Medicine and at the Department of Veterinary Hygiene, Sanitation, and Expertise of Odesa State Agrarian University. The study found that the content of heavy metals in the water of the Khadzhibey estuary is not constant and fluctuates depending on the season. The maximum levels of heavy metals are observed in summer (plumbum and cadmium) and autumn (zinc, copper and mercury). It was found that cadmium, plumbum, copper, and mercury content does not exceed the maximum permissible levels for marine fisheries. The zinc content in the water of the Khadzhibey estuary exceeds the maximum permitted concentration by 2.65%. The zinc content in the studied water samples is a stress factor affecting the meat quality of common carp (Cyprinus carpio) and round goby (Neogobius melanostomus).